National Access to EyeSi Simulation: A Comparative Study Among U.S. Ophthalmology Residency Programs - Oseni, Jessinta; Adebayo, Ayobami; Raval, Nilesh; Moon, Jee Young; Juthani, Viral; Chuck, Roy S.; Shrivastava, Anurag (Journal of Academic Ophthalmology, 2023)
Purpose The aim of this study was to evaluate regional disparities in access to EyeSi surgical simulation training among U.S. ophthalmology residency programs.Methods Access to EyeSi simulation was determined from sales data (2021) provided by VRMagic. Key demographic metrics of the primary counties of U.S. residency training programs were retrieved from the U.S. Census Bureau Database (2019) and PolicyMap (2021). Demographic metrics, Veterans Affairs (VA) hospital affiliation, and Doximity residency program ranking (2021) were compared using the Mann–Whitney U test and Fisher's exact test.Results A total of 124 residency training programs across 95 U.S. counties were included. Regional density (number of EyeSi simulators/million people) was calculated; the west had a significantly lower density when compared with the northeast (NE), south, and midwest (0.4 vs 1.0, 1.3, 1.1, respectively). In the NE, there was a significantly lower population of Blacks (p = 0.01), Hispanics (p = 0.028), and Native Americans (p = 0.008) residing in counties with access to EyeSi, compared with counties without EyeSi access. Programs with EyeSi access (N = 95) had a median Doximity ranking of 52.5, whereas programs without EyeSi access (N = 35) had a lower median ranking of 94 (p < 0.001).Conclusion Our analysis demonstrates significant disparities in access to EyeSi simulation training in the United States that could disproportionately impact minority communities. Access to an EyeSi simulator was associated with higher residency ranking independent of VA affiliation.
Keywords: EyeSi simulation; distribution; ophthalmology residency programs; program ranking; VA affiliation